2023
DOI: 10.3390/ma16062477
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Cyclic Dipeptide Functionalized Nanofibers for Thermal Sensing and Energy Harvesting

Abstract: Nanostructured dipeptide self-assemblies exhibiting quantum confinement are of great interest due to their potential applications in the field of materials science as optoelectronic materials for energy harvesting devices. Cyclic dipeptides are an emerging outstanding group of ring-shaped dipeptides, which, because of multiple interactions, self-assemble in supramolecular structures with different morphologies showing quantum confinement and photoluminescence. Chiral cyclic dipeptides may also display piezoele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
4
6
1
Order By: Relevance
“…We may therefore conclude that the incorporation of the dipeptide in a PCL polymer matrix favored the manifestation of its polar proprieties. Recently, we have reported the pyroelectric coefficient of Cyclo (L-Trp-L-Trp)@PLLA and Cyclo (L-Trp-L-Trp)@PCL nanofibers [4], whose values are, respectively, 36×10 -6 Cm -2 K -1 at 315 K and 35×10 -6 Cm -2 K -1 at 323 K, which is an order of magnitude higher than that reported in that work for Boc-Phe-Leu@PCL. Significantly, a study reported a pyroelectric coefficient of approximately 2×10 -6 Cm -2 K -1 for a diphenylalanine microtubes [32] that is the same reported in this work for Boc-Phe-Leu@PCL.…”
Section: Pyroelectric Propertiesmentioning
confidence: 50%
See 2 more Smart Citations
“…We may therefore conclude that the incorporation of the dipeptide in a PCL polymer matrix favored the manifestation of its polar proprieties. Recently, we have reported the pyroelectric coefficient of Cyclo (L-Trp-L-Trp)@PLLA and Cyclo (L-Trp-L-Trp)@PCL nanofibers [4], whose values are, respectively, 36×10 -6 Cm -2 K -1 at 315 K and 35×10 -6 Cm -2 K -1 at 323 K, which is an order of magnitude higher than that reported in that work for Boc-Phe-Leu@PCL. Significantly, a study reported a pyroelectric coefficient of approximately 2×10 -6 Cm -2 K -1 for a diphenylalanine microtubes [32] that is the same reported in this work for Boc-Phe-Leu@PCL.…”
Section: Pyroelectric Propertiesmentioning
confidence: 50%
“…Peptide nanomaterials offer a range of desirable characteristics, including thermal and mechanical stability, electrical conductivity, piezoelectricity, and optical properties, making them suitable for incorporation into (nano)devices. When dipeptide nanomaterials are integrated into polymeric nanofibers, they create new composite-based materials that exhibit enhanced thermal and mechanical stability [3,4]. These dipeptides can be easily modified through functionalization, resulting in bioinspired and durable semiconductor/dielectric materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromechanical coupling is a phenomenon exhibited by amino acids [ 15 , 16 , 17 ], dipeptides such as chiral diphenylalanine nanotubes [ 18 ] and its derivatives [ 19 , 20 ] and cyclic dipeptides such as cyclo-L-phenylalanine-L-tryptophan [ 21 ], cyclo-glycine-L-tryptophan [ 22 ] and cyclo-L-tryptophan-L-tryptophan [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is prevalent global pollution with plastics at the macro-and microscales; therefore, it is necessary to limit this kind of pollution in the environment. This is why, in recent years, so many studies have proposed that the use of biopolymers can compete with traditional plastic polymers in many crucial fields such as medicine [1][2][3], the food industry [4,5], safety [6], and energy storage [7][8][9].…”
Section: Introductionmentioning
confidence: 99%